Molecular and Clinicopathological Features of Gastrointestinal Stromal Tumors in Vietnamese Patients - Ngo, Quoc Dat (J Pathol Transl Med, 2019)
BACKGROUND: Gastrointestinal stromal tumors (GISTs) are the most frequent mesenchymal neoplasms of the gastrointestinal tract. Management of GIST patients is currently based on clinicopathological features and associated genetic changes. However, the detailed characteristics and molecular genetic features of GISTs have not yet been described in the Vietnamese population. METHODS: We first identified 155 patients with primary GIST who underwent surgery with primary curative intent between 2011 and 2014 at University Medical Center at Ho Chi Minh City, Vietnam. We evaluated the clinicopathological features and immunohistochemical reactivity to p53 and Ki-67 in these patients. Additionally, KIT genotyping was performed in 100 cases. RESULTS: The largest proportion of GISTs was classified as high-risk (43.2%). Of the 155 GISTs, 52 (33.5%) were positive for Ki-67, and 58 (37.4%) were positive for p53. The expression of Ki-67 and p53 were correlated with mitotic rate, tumor size, risk assessment, and tumor stage. Out of 100 GIST cases, KIT mutation was found in 68%, of which 62 (91.2%) were found in exon 11, two (2.9%) in exon 9, and four (5.8%) in exon 17. No mutation in exon 13 was identified. Additionally, KIT mutations did not correlate with any clinicopathological features. CONCLUSIONS: The expression of Ki-67 and p53 were associated with high-risk tumors. Mutations in exon 11 were the most commonly found, followed by exon 17 and exon 9. Additionally, KIT mutation status was not correlated with any recognized clinicopathological features.